2010
DOI: 10.4049/jimmunol.1000296
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Role of Mammalian Target of Rapamycin in Human Dendritic Cell Function and Differentiation

Abstract: The mammalian target of rapamycin (mTOR) regulates cell growth and survival and exists as rapamycin-sensitive mTOR complex (mTORC) 1 and as rapamycin-insensitive mTORC2. Although mTOR is a well-known regulator of diverse immune cells, its detailed role in human dendritic cell (DC) function and differentiation is only incompletely understood. In this study, we demonstrate divergent roles of mTOR during activation and differentiation of myeloid DCs (mDCs) and monocyte-derived DCs (moDCs). Inhibition of mTORC1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
234
4
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(268 citation statements)
references
References 68 publications
27
234
4
3
Order By: Relevance
“…In TSC2-deficient MEFs, pro-inflammatory responses are decreased due to impaired IKK activation and NF-kB translation to the nuclei 44 . However, other studies reported that Rapa treatment enhances IL-12 production in myeloid DCs by promoting NF-kB activation but inhibits IL-12 production in monocyte-derived DCs and bone marrow-derived DCs 20,45 .…”
Section: Discussionmentioning
confidence: 98%
“…In TSC2-deficient MEFs, pro-inflammatory responses are decreased due to impaired IKK activation and NF-kB translation to the nuclei 44 . However, other studies reported that Rapa treatment enhances IL-12 production in myeloid DCs by promoting NF-kB activation but inhibits IL-12 production in monocyte-derived DCs and bone marrow-derived DCs 20,45 .…”
Section: Discussionmentioning
confidence: 98%
“…Previous findings showed that rapamycin suppressed immunostimulatory molecules and the allostimulatory potential of LPS-stimulated DC. 26 However, when we investigated by flow cytometry analysis the immunophenotype of DC, no major differences were observed on the Mtb-induced expression of the molecules involved in T cell activation, such as CD86, CD83, HLA-DR and CD38 (Table 1). Also, no modulation of Mtb-induced tumor necrosis factor (TNF) production was observed upon rapamycin treatment (Fig.…”
Section: Mtb and Bcg Have Different Impacts On The Autophagic Processmentioning
confidence: 99%
“…Given the inhibitory effect exerted by IL4 on autophagy 25 and the activation of MTOR pathway by CSF2 and IL4 along monocyte-derived DC, 26 we compared in preliminary experiments the effect of Mtb infection on the autophagic process in the presence of CSF2 and IL4 or following the replacement of the differentiating medium 20 h before infection. Having found that both the basal and Mtbdriven autophagic response was altered by the presence of IL4 and CSF2 (data not shown), we decided to perform our study in DC starved from these differentiating cytokines.…”
Section: Mtb and Bcg Have Different Impacts On The Autophagic Processmentioning
confidence: 99%
“…8 Mucosal pDC and mDC have been investigated in only a few human studies, although accumulation of activated DC at the sites of inflammation may contribute to the pathogenesis of human inflammatory bowel disease (IBD). 6,[9][10][11][12] Reduced proportions of immature pDC have been found in the peripheral blood (PB) of patients with IBD, suggesting their recruitment to inflamed mucosal tissues. 13,14 Additionally, mesenteric lymph node (MLN) pDC express the chemokine receptor CCR6, which could explain musosal accumulation at inflamed tissue sites as a consequence of up-regulated mucosal addressines such as CCL20 or mucosal addressin cell adhesion molecule-1.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%